2023
DOI: 10.1002/jsfa.12424
|View full text |Cite
|
Sign up to set email alerts
|

In search of better snacks: ohmic‐heating nixtamalized flour and amaranth addition increase the nutraceutical and nutritional potential of vegetable‐enriched tortilla chips

Abstract: BACKGROUND Nixtamalized flour snacks such as tortilla chips are widely consumed across the world, but they are nutritionally poor and contribute to obesity and other non‐communicable diseases. The production of healthy versions of such snacks, by incorporating vegetables and improving the quality of the flours used in their formulation, could help address these nutritional challenges. This study compared the fortification of baked tortilla chips with vegetable leaf powders (kale and wild amaranth at 0%, 4%, 8%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…Such composite flour samples were used to make tortillas of regular sizes. Round tortillas of 20 cm diameter were developed by following the already reported methods of Kapoor et al [14] and Dominguiz-Hernandez et al [15]. Briefly, 100g of each of composite wheat flour samples (0%, 2%, 4% and 6 %) was mixed with desired quantity of distilled water to make viscoelastic dough; amount of water taken up by each sample was regarded as % water absorption (Table 1).…”
Section: Preparation Of Supplemented Tortillasmentioning
confidence: 99%
“…Such composite flour samples were used to make tortillas of regular sizes. Round tortillas of 20 cm diameter were developed by following the already reported methods of Kapoor et al [14] and Dominguiz-Hernandez et al [15]. Briefly, 100g of each of composite wheat flour samples (0%, 2%, 4% and 6 %) was mixed with desired quantity of distilled water to make viscoelastic dough; amount of water taken up by each sample was regarded as % water absorption (Table 1).…”
Section: Preparation Of Supplemented Tortillasmentioning
confidence: 99%
“…On the other hand, although ready-to-eat snacks offer considerable market potential, they are perceived as unhealthy products due to their high energetic value, their salt and fat content, and the presence of trans-saturated fatty acids. Some studies reported in the literature have tested the feasibility of different drying treatments to monitor the modifications in physicochemical parameters of vegetable-based chips such as potato [ 31 , 32 ], pumpkin [ 33 ], jujube [ 34 ], or apples [ 35 ]. However, the addition of natural antioxidant extracts based on agricultural byproducts as a natural ingredient has not been extensively reported.…”
Section: Introductionmentioning
confidence: 99%
“…Ассортимент в основном представлен макаронными изделиями (вермишель, спагетти и др.) [13][14][15][16], продуктами хлебопекарного производства (хлеб [17], печенье [18,19]) и снеками [20,21]. Макаронные изделия получают с включением в состав 10-30% амарантовой муки [13][14][15][16].…”
unclassified